Implimentasi Tri Hita Karana dalam Pendidikan Pratikum Seni Kuliner - Wiryanata, I Gusti Ngurah Agung; Suastra, I Wayan; Arnyana, Ida Bagus Putu (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
This study aims to determine the implementation of Tri Hita Karana in the process of practicum in the culinary art study program. Vocational universities are required to design and implement innovative learning processes so that students can achieve learning outcomes including character, aspects of attitudes, knowledge and skills optimally. Tri Hita Karana concept of harmony of human relationship with God, man and nature. Practicum of Culinary Art Study Program in the kitchen with an uncomfortable atmosphere, the role of Tri Hita Karana as a foundation in daily activities. The research methodology uses qualitative analysis of case studies, while the data are obtained by in-depth interviews and observations. Data is a lecturer and third-semester student of Culinary Arts Bali Tourism Polytechnic. Implementation of Tri Hita Karana in a practicum in the study program Seni kuliner: (a) Parhyangan, installing curtains, praying together, and banten saiban every day. (b) Pawongan, by communicating with stakeholders. (c) Palemahan, students and lecturers carry out the cleaning of practical equipment, sorting organic waste and handling plastic waste. The application of Tri Hita Karana concept in carrying out practicum will build student character and spirituality.